2018
DOI: 10.1002/pro.3362
|View full text |Cite
|
Sign up to set email alerts
|

Penetration into membrane of amino‐terminal region of SecA when associated with SecYEG in active complexes

Abstract: The general secretory (Sec) system of Escherichia coli translocates both periplasmic and outer membrane proteins through the cytoplasmic membrane. The pathway through the membrane is provided by a highly conserved translocon, which in E. coli comprises two heterotrimeric integral membrane complexes, SecY, SecE, and SecG (SecYEG), and SecD, SecF, and YajC (SecDF/YajC). SecA is an associated ATPase that is essential to the function of the Sec system. SecA plays two roles, it targets precursors to the translocon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 60 publications
2
31
0
Order By: Relevance
“…Recently, Koch et al (14) utilized single copies of SecYEG reconstituted into nanodiscs of differing lipid content in order to show that SecA gains access to SecYEG translocons via a lipidbound intermediate utilizing SecA protein's amphipathic lipid-binding N terminus. More recently, Findik et al (15) showed that this region of SecA assumed different conformations in PLYEG and PLYEG•SecA liposomes, where the N terminus penetrated the lipid bilayer more deeply in the former case, while it was found in a more shallow state, parallel to the plane of the membrane at the interface between the polar and hydrophobic regions, in the latter case. These formative studies help to define the role of the SecA N-terminal ϳ20 residues as a molecular switch that alternates between two lipid-inserted conformations that turn off and on its high-affinity SecYEG binding and translocation ATPase activities (16,17).…”
mentioning
confidence: 99%
“…Recently, Koch et al (14) utilized single copies of SecYEG reconstituted into nanodiscs of differing lipid content in order to show that SecA gains access to SecYEG translocons via a lipidbound intermediate utilizing SecA protein's amphipathic lipid-binding N terminus. More recently, Findik et al (15) showed that this region of SecA assumed different conformations in PLYEG and PLYEG•SecA liposomes, where the N terminus penetrated the lipid bilayer more deeply in the former case, while it was found in a more shallow state, parallel to the plane of the membrane at the interface between the polar and hydrophobic regions, in the latter case. These formative studies help to define the role of the SecA N-terminal ϳ20 residues as a molecular switch that alternates between two lipid-inserted conformations that turn off and on its high-affinity SecYEG binding and translocation ATPase activities (16,17).…”
mentioning
confidence: 99%
“…3 The transition between state I and II may be associated with the insertion of the N-terminus into the lipid membrane as previously suggested. 4 The model does not refer to the SecA dimer, because it is (i) apparently unable to bind to the membrane surface 36,37 , and (ii) dissociates the presence of acidic lipids 25 . Reports about the functionality of covalently linked SecA dimers 5,42 do not challenge the conclusion, because they do not contain evidence that the dimer may bind to the lipid in the absence of SecYEG.…”
Section: Discussionmentioning
confidence: 99%
“…44 Our model suggests that the insertion of SecA's N-terminus into the lipid membrane hinders a deep penetration of SecA's two-helix finger into SecYEG. Thus, SecA is trapped shuttling in between state IV and V. However, it does not require a major conformational change 2,4 to strongly bind to SecYEG as in state III the N-terminus is functioning solely as membrane-tether 7 that is electrostatically linked to the membrane, but not inserted into it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations